2023
DOI: 10.1021/acs.jafc.3c00909
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Elucidation of Flavor Chemistry

Abstract: Flavor molecules are commonly used in the food industry to enhance product quality and consumer experiences but are associated with potential human health risks, highlighting the need for safer alternatives. To address these health-associated challenges and promote reasonable application, several databases for flavor molecules have been constructed. However, no existing studies have comprehensively summarized these data resources according to quality, focused fields, and potential gaps. Here, we systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…ML models are usually considered “black boxes” due to their poor interpretability. , In response, previous studies have used a SHAP-based approach to identify the most important molecular descriptors that affect the PCFs of chemicals . However, it could not provide clear insights on, for example, PCF-intensive substructures and raw materials to guide the design of more sustainable molecules and processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ML models are usually considered “black boxes” due to their poor interpretability. , In response, previous studies have used a SHAP-based approach to identify the most important molecular descriptors that affect the PCFs of chemicals . However, it could not provide clear insights on, for example, PCF-intensive substructures and raw materials to guide the design of more sustainable molecules and processes.…”
Section: Resultsmentioning
confidence: 99%
“…The contamination of proxy data is transmitted to these pre-LCA tools, compromising their performance. Furthermore, while ML has been successfully applied in many fields, interpretability remains challenging for ML-based models. , Previous tools used Shapley additive explanations (SHAP) to identify the critical molecular descriptors that are relevant to PCFs. However, the detailed correlations between PCFs and functional groups and substructures cannot be distinctly quantified, which limits their application in the design of more sustainable molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The data for the article was downloaded from the LRI & Odour Database—Odour Data, Flavornet and The Good Scents Company Information System, as well as the paper by Hatanaka et al [ 2 , 21 ]. We extracted 9944 non-green odor molecules and 642 green odor molecules from the database, as indicated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Given the great potential of fermentation products in antiseptic, antioxidation, immunity regulation, and other aspects, scientists have tried to identify the metabolic products of microorganisms in the fermentation process . A food component may undergo a variety of structural modifications causing unknown changes in biological activity under the action of various fermentation strains . Previous studies have shown that there are thousands of novel metabolites produced in the food fermentation process .…”
Section: Introductionmentioning
confidence: 99%